2011
DOI: 10.1039/c1sc00323b
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotubes shell decorating porous silicate materials: A general platform for studying the interaction of carbon nanotubes with photoactive molecules

Abstract: Single-walled carbon nanotubes (SWCNTs) have been deposited onto the external surface of porous silicate materials by deposition from a solution of individualized, protonated SWCNTs in chlorosulfonic acid. It is demonstrated that the deposited SWCNTs can be deprotonated on the silicate surface, yielding a microporous or mesoporous material with individual or small bundles of SWCNTs. These carbon nanotubes present all the spectral characteristics of pristine SWCNTs, including van Hove transitions, Raman and NIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In a previous publication we showed that SWCNTs protonated by chlorosulfonic acid (CSA) adhere efficiently to silicon oxide microporous and mesoporous particle surfaces. 25 We hypothesized that a similar behavior could be obtained for such protonated nanotubes (p-SWCNTs) on flat silicon oxide surfaces. Here we report the photophysical and electronic properties of films made by SWCNT deposition from CSA onto flat fused silica windows (Figure 1).…”
Section: June 08 2012mentioning
confidence: 84%
See 1 more Smart Citation
“…In a previous publication we showed that SWCNTs protonated by chlorosulfonic acid (CSA) adhere efficiently to silicon oxide microporous and mesoporous particle surfaces. 25 We hypothesized that a similar behavior could be obtained for such protonated nanotubes (p-SWCNTs) on flat silicon oxide surfaces. Here we report the photophysical and electronic properties of films made by SWCNT deposition from CSA onto flat fused silica windows (Figure 1).…”
Section: June 08 2012mentioning
confidence: 84%
“…26,27 In a previous article, we reported that the bulk NIRphotoluminescence of p-SWCNTs can be regenerated by deprotonating the SWCNT surface. 25 To determine whether this process also occurs for CNTs deposited on fused silica, a film was made from a dilute SWCNT CSA solution and then treated with diethyl ether. Figure 2 shows the fluorescence image of such a film.…”
Section: Resultsmentioning
confidence: 99%
“…To exploit the outstanding properties of individualized SWCNTs, one has to overcome the formidable van der Waals attractions among tubes (0.5 eV/nm), which is the main obstacle to make uniform and stable dispersions. Over the past few years, many effective dispersion technologies have been developed, including covalent sidewall functionalization, noncovalent interaction-assisted dispersion, and superacid dissolution. , Another intriguing way to disperse SWCNTs is by forming SWCNT polyelectrolytes, where nanotubes are negatively charged by reduction by alkali metals. Upon adding polar aprotic solvents, the negatively charged sidewalls of the nanotubes induce Coulombic repulsion between tubes, resulting in their spontaneous dissolution. Early work in this field showed that SWCNT polyelectrolytes can be synthesized by metallic lithium reduction. , Later, Pénicaud reported the use of other alkali metals and showed that SWCNT salts [A(THF)] n CNT (A = Li, Na, K) could spontaneously dissolve in a series of aprotic organic solvent, such as dimethyl sulfoxide (DMSO) and sulfolane. However, the reported solubility of HiPco SWCNT polyelectrolytes was relatively low (0.4 mg/g in DMSO), which prevents the formation of a liquid crystal and limits its further processing into macroscopic assembly such as SWCNT fibers or sheets …”
mentioning
confidence: 99%
“…[1][2][3][4][5] Among the numerous carbonaceous hybrid materials reported to date, carbon nanotubes (CNTs) containing metal or metal oxide nanoparticles (NPs) have been intensively studied owing to their high electrical conductivity, their large surface area and their porosity. [5][6][7][8][9][10] Hybrid CNTs have been synthesized by established methods including chemical vapor deposition (CVD), 11 electrospinning 12 and hard template wetting. 13 Block copolymers (BCPs) mixed with carbon precursors like phenolic resins were used as structure-directing soft templates in the preparation of mesoporous carbonaceous thin films or monoliths with well-defined long-range periodicity, 14,15 as well as in the synthesis of mesoporous carbon nanorods inside shape-defining nanoporous hard templates such as anodic aluminium oxide.…”
mentioning
confidence: 99%